From oviparity to viviparity: a preliminary note on the morphometric differentiation between oviparous and viviparous species assigned to the genus Liolaemus (Reptilia, Squamata, Liolaemidae) - Cei, José Miguel Alfredo María (2003)
Embryonic growth requires a considerable internal space in viviparous female lizards and this need for space should be reflected in their external morphometry. External morphological differences associated with the reproductive mode in 12 viviparous and 18 oviparous species of Liolaemus lizards were identified. Size differences between viviparous and oviparous species were elucidated by axilla-groin/snout-vent relationship. Axilla-groin distance, considered a size estimator of visceral cavity, surpassed 50% of snout-vent length in viviparous females, while it is always less than 50% in oviparous females. This difference between the two reproductive modes is statistically significant.